PENGADAAN TANAH UNTUK PEMBANGUNAN PROYEK PEMERINTAH SETELAH BERLAKUNYA PERATURAN PRESIDEN NOMOR 65 TAHUN 2006 - S Sarsiti (Authentica, 2018)
The increase in the human population will also increase the need for land, but this cannot be accompanied by an increase in the existing land area. This paper discusses land acquisition for government project development after the enactment of Presidential Regulation Number 65 of 2006; and legal remedies if there is no agreement in the process of land acquisition. These legal issues are approached by normative methods with conceptual approaches and legislative approaches. Land acquisition for development for Government projects is carried out through the process of Releasing Legal Rights if no agreement is reached, then the Regent / Mayor or Governor or Minister of Home Affairs according to the authority submits a proposal for a settlement by revoking land rights.Keywords: land acquisition, a release of rights, revocation of rights.